MiR858b Inhibits Proanthocyanidin Accumulation by the Repression of DkMYB19 and DkMYB20 in Persimmon - Yang, Sichao; Zhang, Meng; Xu, Liqing; Luo, Zhengrong; Zhang, Qinglin (Frontiers in Plant Science, 2020)
Persimmon proanthocyanidin (PA) biosynthesis is controlled by structural genes and regulated by transcription factors. MicroRNAs are a key factor involved in regulating gene expression at the posttranscriptional level whose functions in persimmon PA biosynthesis are poorly understood. Here, we identified a microRNA, miR858b, that putatively targets two R2R3-MYB transcription factors, DkMYB19 and DkMYB20. DkMYB19, DkMYB20 and miR858b showed divergent expression patterns during fruit development, and the interaction between miR858b and DkMYB19 or DkMYB20 was experimentally validated by 5’ RNA ligase-mediated RACE, LUC enzyme activity analysis and GUS signal detection. The DkMYB19 localized to the nucleus as well as cytoplasm and DkMYB20 localized to the nucleus. The overexpression of miR858b led to the downregulation of DkMYB19 and DkMYB20, which reduced the content of PA, whereas a reduction in miR858b activity upregulated DkMYB19 and DkMYB20, resulting in a high content of PA in leaves transiently expressing a small tandem target mimic construct for blocking miR858 (STTM858b) in vivo. The transient transformation of miR858b in fruit discs in vitro also reduced the content of PA, while the content of PA increased under the transient transformation of fruit discs with STTM858b, DkMYB19 or DkMYB20. A similar phenomenon was observed upon the overexpression of miR858b in wild-type Arabidopsis and DkMYB19 or DkMYB20 in persimmon leaf calli. These findings suggested that miR858b repressed the expression of DkMYB19 and DkMYB20, which contributed to PA accumulation in persimmon.